Management of Ahlussunnah wal Jama'ah-Based Curriculum Development in Islamic Education Best Practice - Samsul Arifin; M. Aqil Fahmi Sanjani (Al-Qalam Institute, 2024)
This study examines the development of the Ahlussunnah Wal Jama'ah value-based curriculum at MI At-Taqwa Bondowoso, focusing on planning, implementing, and evaluating the curriculum. The main problem is how Ahlussunnah Wal Jama'ah's values are applied in a curriculum that prioritizes academic aspects and the formation of students' character. This research is relevant because although there is much literature on religion-based education, applying these values in students' daily lives in madrasas is still minimally explored. The research method used is a qualitative approach with case studies, where data is obtained through in-depth interviews with teachers, madrasah heads, and parents of students, as well as analysis of documentation and findings in the field. The study results show that curriculum planning is carried out collaboratively between teachers, parents, and the community, aiming to create a balance between academic intelligence and character building. The implementation of the curriculum is reflected in students' daily activities, such as congregational prayers and routine recitations. Curriculum evaluations are carried out periodically to ensure suitability with student development. These findings contribute to understanding how Ahlussunnah Wal Jama'ah-based education can be implemented holistically in madrasas.